The parakeet - Portet, Sébastien 1974- (The Pennsylvania State University Press/Graphic Mundi, 2021)
"An account in graphic novel format, based on the author's own experiences, of a boy coping with his mother's suffering from bipolar disorder and schizophrenia, showing how mental illness can both tear families apart and reaffirm the bonds of love"--
Keywords: Manisch-depressive Krankheit; Mutter; Schizophrenie; Junge; Bipolar disorder / Comic books, strips, etc; Schizophrenia / Comic books, strips, etc; Dysfunctional families / Psychological aspects / Comic books, strips, etc; Mother and child / Comic books, strips, etc; Children of depressed persons / Comic books, strips, etc; Children of the mentally ill / Comic books, strips, etc; Medicine / Comic books, strips, etc; France / Comic books, strips, etc; Schizophrenia; Mother and child; Bipolar Disorder; Child of Impaired Parents; Mother-Child Relations; France; Schizophrenic Psychology; Children of depressed persons; Children of the mentally ill; Graphic Novels; Graphic medicine (Comics); Autobiographical comics; Comics (Graphic works); Comic